Analysis and experiment of entanglement relationship between straw and rotating rollers of the grass curtain machine - Dong Wang; Dian Wang; Hongrui Liu (Smart Agricultural Technology)
In order to clarify the entanglement relationship between the grass curtain machine’s rotating rollers and the straw, and to optimize the structure of the rotating roller to reduce entanglement. This study established a dynamic model of straw wrap the rotating roller based on discrete element technology, using the compressive force received by the rotating roller as the evaluation index for the entanglement degree. Through this model, five process stages of straw entanglement around the rotating roller were found, in addition, the process of straw entanglement the rotating roller was mathematically modeled. The modeling confirmed that the length of the straw(LS), the diameter of the rotating roller(DR), and the number of straws(NS) are the main factors influencing entanglement. Furthermore, an orthogonal experiment based on a test platform was designed to validate the rationality of the simulation results, variance analysis and range analysis were employed to process the experimental data. The results show that: (1) factor A (R = 6.67, p = 0.028), factor B (R = 8.67, p = 0.016), and factor C (R = 7.8, p = 0.020), which correspond to DR, LS, and NS respectively, verify the validity of the simulation model's conclusions, and the priority of these factors is LS > NS > DR. (2) the degree of entanglement is directly proportional to LS, inversely proportional to the DR, and directly proportional to the NS. (3) When the diameter of the rotating roller is 200 mm, the straw mass is 10 g, and the straw length is 855 mm, the entanglement rate is 26 %, and the rotating roller is least likely to be entangled.